HIV infection among newly Daignosed TB patients in southwestern Nigeria: A multi-DOTS center study (2013)
Backgroud: The burden of TB and HIV infection is estimated to be about 512/100,000 and 3,000,000 people respectively. However, accurate data on TB/HIV co-morbidity in different parts of Nigeria were not available due to limited access to HIV Counseling and Testing (HCT) by individuals with TB infection. This study was designed to determine the true rate of HIV infection among newly diagnosed TB patients by providing comprehensive HCT services in 43 DOTS centers in Oyo State, Southwestern Nigeria. Methods: All patients meeting the case definition for TB suspects who presented at each of the 43 DOTS Centres were counselled and those who consented tested for presence of HIV antibodies using HIV 1/2 Determine, Unigold and Stat-Pak rapid test kits in a serial algorithm. Results: A total of 13,109 TB positive patients were enrolled for the study, out of which 1605 (12.3%) tested positive for HIV antibodies. HIV infection was higher among female (15.5%) than male (9.5%) TB patients (p < 0.05). The rates also varied among the age groups, ranging from 4.3% in the 10 - 19 years to 18.0% in the 40 - 49 years age group. A relatively high rate (10.5%) of HIV infection was found among children less than ten years of age. Conclusion: The results of this work show the true burden of TB/HIV in any region in Nigeria for the first time. Higher rate of TB/HIV co-infection among female patients and children are significant and important factors that should be considered in the planning of intervention measures in Nigeria and other TB and HIV endemic countries in Africa.